2021
DOI: 10.1186/s13014-021-01806-5
|View full text |Cite
|
Sign up to set email alerts
|

Variation of heart and lung radiation doses according to setup uncertainty in left breast cancer

Abstract: Purpose Breast radiotherapy set-up is often uncertain. Actual dose distribution to normal tissues could be different from planned dose distribution. The objective of this study was to investigate such difference in dose distribution according to the extent of set-up error in breast radiotherapy. Materials and methods A total of 50 Gy with fraction size of 2 Gy was given to 30 left breasts with different set-ups applying a deep inspiration breath h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…CBCT‐guided radiotherapy has the potential to reduce setup errors, improve radiotherapy accuracy, minimize the external margin of the PTV, and decrease the dose delivered to the OARs. 19 , 20 , 21 However, the accuracy of image registration is influenced by various factors, including the registration algorithm, 22 the region of interest, 10 , 23 and the evaluation criteria. 24 Richter et al 22 reported that gray‐level registration has higher accuracy registration than bony registration.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT‐guided radiotherapy has the potential to reduce setup errors, improve radiotherapy accuracy, minimize the external margin of the PTV, and decrease the dose delivered to the OARs. 19 , 20 , 21 However, the accuracy of image registration is influenced by various factors, including the registration algorithm, 22 the region of interest, 10 , 23 and the evaluation criteria. 24 Richter et al 22 reported that gray‐level registration has higher accuracy registration than bony registration.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have focused on the impact of translational setup errors and roll or yaw rotations on the dose distribution in breast cancer radiotherapy. 12,24,25 Therefore, the rotational setup errors in 3 directions were simulated simultaneously in this study. In dosimetry comparisons of the PTV, a 5% change in the dosimetry was judged as acceptable variation.…”
Section: Dosimetry Variations For the Breast Target And Oars With Or ...mentioning
confidence: 99%